2007
DOI: 10.1091/mbc.e07-05-0491
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide Bond-mediated Multimerization of Ask1 and Its Reduction by Thioredoxin-1 Regulate H2O2-induced c-Jun NH2-terminal Kinase Activation and Apoptosis

Abstract: Apoptosis signal-regulated kinase-1 (Ask1) lies upstream of a major redox-sensitive pathway leading to the activation of Jun NH 2 -terminal kinase (JNK) and the induction of apoptosis. We found that cell exposure to H 2 O 2 caused the rapid oxidation of Ask1, leading to its multimerization through the formation of interchain disulfide bonds. Oxidized Ask1 was fully reduced within minutes after induction by H 2 O 2 . During this reduction, the thiol-disulfide oxidoreductase thioredoxin-1 (Trx1) became covalentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
140
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(150 citation statements)
references
References 51 publications
7
140
0
3
Order By: Relevance
“…Previously, it has been suggested that the interaction of Trx with g5p and ASK1 target proteins is critically dependent on the redox state of Trx, despite being independent of Trx oxido-reductase function (9,20). However, later studies have proposed alternative models possibly involving the oxidoreductase function of Trx in regulation of these proteins (36,37). In light of these studies and others, the absolute dependence of these interactions on the Trx redox-state may need to be reevaluated using a direct solution-based measurement of noncovalent interaction between Trx and these target proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been suggested that the interaction of Trx with g5p and ASK1 target proteins is critically dependent on the redox state of Trx, despite being independent of Trx oxido-reductase function (9,20). However, later studies have proposed alternative models possibly involving the oxidoreductase function of Trx in regulation of these proteins (36,37). In light of these studies and others, the absolute dependence of these interactions on the Trx redox-state may need to be reevaluated using a direct solution-based measurement of noncovalent interaction between Trx and these target proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Formation of DJ-1-ASK1-mixed Disulfides-The dependence of DJ-1 binding to ASK1 on the central redox residue prompted us to consider mixed disulfide formation between ASK1 and DJ-1, because it was recently shown for thioredoxin 1 (Trx1) (35). HEK293E cells were transiently co-transfected with ASK1/HA and Myc/DJ-1 variants as above, but in this experiment ASK1 complexes immunoprecipitated with anti-HA were resolved by non-reducing SDS-PAGE.…”
Section: Mutagenesis Of Dj-1 Cysteine Andmentioning
confidence: 99%
“…Studies conducted by Nadeau et al, revealed an alternative mechanism for the function of Trx1 in the regulation of ASK1 in response to H 2 O 2 . These studies demonstrated that H 2 O 2 induces ASK1 oxidation leading to the formation of interchain disulfide bond-linked ASK1 multimers [25,26]. These authors demonstrated that changing all oxidation sensitive cysteine residues responsible for disulfide bond-linked multimers, prevented H 2 O 2 -induced ASK1 proapototic activity.…”
Section: Modulation Of Ask1 Activity By Postranslational Modificationmentioning
confidence: 91%
“…Recently, redox sensitive molecules such as the Parkinson's associated protein DJ-1 (a.k.a PARK7) and Peroxiredoxin-2 have also been shown to attenuate ASK1 activity in response to toxic stress in dopaminergic neurons [27][28][29]. Interestingly, mutation analyses demonstrated, that the ER stress-inducing agent thapsigargin, while inducing ASK1 activation (as determined by Thr838 phosphorylation) was observed to be independent of Cys250 [25]. In attempting to address the role of Cys250 and the role of Trx1 in regulating Fig.…”
Section: Modulation Of Ask1 Activity By Postranslational Modificationmentioning
confidence: 99%
See 1 more Smart Citation